A Literature Review: Barriers Of Pharmaceutical Logistics Management In Hospitals During Covid-19 Pandemic - Ahmad Haidar Mushoddaq (Universitas Bhakti Kencana, 2022)
Pharmaceutical logistics management is very important to maintain the availability of pharmacies, however the covid-19 pandemic hampered the management process. This study identified the process of pharmaceutical logistics management in hospitals during covid-19 pandemic. Used a literature review method, articles were collected from Google Scholat database published from 2020 to 2022. 10 articles were collected, but only 7 of them are discussed because of their relevant topics. Most of articles explained that the barriers found in three out of nine phases in the logistics management cycle. These phases are needs planning, procurement, and storage. Instead of found the barriers in all the phases, every hospital has its own barriers depends on the condition at that moment. The author conclude that the main barrier in the process of pharmaceutical logistics management in hospitals during covid-19 pandemic is the decreasing number of patients. From this barrier has an impact on other losses. Thus, this moment must be an important lesson for managers to manage pharmaceutical logistics in the future.